EKSPLORASI AMSAL DALAM SURAH AL-BAQARAH SEBAGAI INSTRUMEN PEMBINAAN AKHLAK ISLAMI - Pephitasya Juliana; Achmad Abubakar; Halimah Basri (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to explore the meaning and function of proverbs (parables) in Surah Al-Baqarah as an instrument for fostering Islamic morals. Proverbs in the Qur’an are one of the communicative and pedagogical methods used to convey moral and spiritual values concretely, so that the moral messages can be understood deeply and applied in daily life. Surah Al-Baqarah was chosen because it contains various parables rich in ethical and theological meanings, such as the parable of the hypocrites, the one who spends wealth ostentatiously, and the parable of the fly, which illustrates human weakness before Allah's power. The approach in this study uses a qualitative-descriptive method with library research through thematic analysis. The results of this study indicate that proverbs in Surah Al-Baqarah function as instruments of moral education that guide humans toward the values of sincerity, patience, honesty, trustworthiness, and reliance on God. Proverbs also serve as a means of spiritual reflection that fosters awareness of the relationship between humans and God as well as with others. This study emphasizes that exploring Quranic proverbs has significant relevance in the development of contemporary Islamic character education and can be used as a conceptual model in moral guidance within Islamic educational institutions.